PEMANFAATAN DAN KONTRIBUSI KEMIRI (ALEURITES MOLUCCANA) SEBAGAI KOMODITI HHBK TERHADAP PENDAPATAN PETANI DI KECAMATAN BONTOCANI KABUPATEN BONE, SULAWESI SELATAN: The Utilization and Contribution of Candlenut (Aleurites Moluccana) as a NTFPs commodity Toward Farmers 'Income in Bontocani District, Bone Regency, South Sulawesi - Baharuddin Baharuddin; Makkarennu Makkarennu; Mughni Rahmi (PERENNIAL, 2021)
Non-timber forest products (NTFPs) have recently had a more excellent economic value than timber forest products. Besides, NTFPs are very diverse. Candlenut (Aleurites moluccana) is one of the NTFP commodities with sufficient economic value to increase income for the communities around the forest. This study aims to determine the utilization and contribution of candlenut businesses to farmers' farm income in Kahu Village, Bontocani District, Bone Regency. The collecting data was done through field observation and interview of 30 respondents. Primary data consists of respondent's identity, condition of candlenut farming, plants other than candlenut, utilization of candlenut, selling price of candlenut, income other than candlenut, and costs incurred (including labor costs and equipment prices) during candlenut management. The results show that the utilization of hazelnut in Kahu Village included candlenut as a spice material and hazelnut as a fuel. As for contributions provided by the candlenut business (Aleurites moluccana) to farmers' farm income in Kahu Village is 46% or Rp.216,333,749 per year.